The Influence Of Effort Of Use, Features Of Products And Promotions On Purchase Decisions And Customers Loyalty: (Study On Customers T-Cash In Surabaya) - Rahjuno Saktio Darpito (Journal of World Conference (JWC), 2019)
This study aims to analyze the influence of ease of use, productfeatures, promotions and purchasing decisions in relation to the loyalty ofT-Cash customers in Surabaya. The research method used is to use an explanatory type of research. With the number of samples, namely the T-Cash users who have not yet been approved, so it is necessary to do the calculation using the lemeshow formula. In the analysis of this study using data collection with the help of filling out questionnaires accompanied by Partial Least Square (PLS) analysis techniques. Research shows the ease of use variables, product features and promotions have a positive and significant relationship simultaneously and partially in its development.